The big bug dug - Serfozo, Mary.; Scherer, Jeffrey (New York, NY : Scholastic Inc, 2003)
Looking for a quiet place to sleep, a big bug digs down past a snake, a slug, a worm, and down even more. Includes punch-out game cards and skill-building activity pages.
"Cartwheel Books."
"With game cards."
BR
Keywords: Insects -- Fiction; Animals -- Fiction; Stories in rhyme